Pengembangan E-LKPD Berbasis Google Sites Terintegrasi Artificial Intelligence pada Elemen Perpajakan Siswa Kelas XII AKL - Permadhani, Reyna Mita; Rohayati, Suci (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
For Class XII AKL students at SMK Negeri 4 Surabaya, the purpose of this project is to create an E-LKPD based on Google Sites combined with Artificial Intelligence (AI) on taxation aspects of Value Added Tax (VAT) and Luxury Goods Sales Tax (PPnBM). Its practicality and student reactions will be examined. This development research employs Thiagarajan's 4-D model, which is restricted to the disseminate phase and comprises the define, design, develop, and disseminate phases. Questionnaires for student responses and expert validation sheets are among the tools utilized. According to validation data, the average score was 92% (